2010
DOI: 10.1007/s00011-010-0213-5
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD40L (CD154) is increased in patients with shock

Abstract: Our data show that sCD40L is increased in patients with shock from septic and non-septic etiologies. However, further studies are needed to delineate the functional significance of sCD40L in the clinical outcome in shock patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…This platelet-dependent activation of neutrophils and subsequent lung damage has recently been shown to be mediated by CD40L released from platelets in abdominal sepsis [11]. In this context, it is also interesting to note that clinical studies have shown that plasma levels of CD40L in the plasma are elevated in patients with sepsis [12,16]. However, the mechanisms regulating sepsis-induced platelet shedding of CD40L are not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This platelet-dependent activation of neutrophils and subsequent lung damage has recently been shown to be mediated by CD40L released from platelets in abdominal sepsis [11]. In this context, it is also interesting to note that clinical studies have shown that plasma levels of CD40L in the plasma are elevated in patients with sepsis [12,16]. However, the mechanisms regulating sepsis-induced platelet shedding of CD40L are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have demonstrated that platelets play an important role in abdominal sepsis [10] by releasing CD40L in the circulation, which, in turn, provokes up-regulation of Mac-1 and promotes pulmonary infiltration of neutrophils and tissue damage [11]. Indeed, a recent study demonstrated that plasma levels of soluble CD40L are markedly elevated in patients with sepsis [12]. In fact, most of the soluble CD40L in plasma is derived from platelets [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that this platelet-dependent pulmonary accumulation of neutrophils is mediated by sCD40L released from platelets in abdominal sepsis [9]. In support of a role of CD40L in sepsis, recent studies have shown that plasma levels of sCD40L are elevated in patients with sepsis, and that platelet shedding of CD40L is regulated by MMPs [25,35,36]. However, the specific mechanism regulating platelet shedding of CD40L in sepsis is not known.…”
Section: Discussionmentioning
confidence: 93%
“…2A). In parallel, surface expression of CD40L on platelets decreased; that is, the mean fluorescence intensity was 49 (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) in sham mice and 32 (29)(30)(31)(32)(33)(34)(35)(36) in septic WT mice (Fig. 2B).…”
mentioning
confidence: 91%
“…8 In support of a role of CD40L in sepsis, elevated plasma levels of soluble CD40L have been observed in patients with sepsis. 33,34 However, the specific signaling mechanisms regulating platelet shedding of CD40L in sepsis are not known. In the present study, we found that Rac1 activity was increased in platelets from septic mice.…”
Section: Discussionmentioning
confidence: 99%